Light‐Emitting Transistors: Multioperation‐Mode Light‐Emitting Field‐Effect Transistors Based on van der Waals Heterostructure (Adv. Mater. 43/2020). Issue 43 (26th October 2020) - Kwon, Junyoung; Shin, June‐Chul; Ryu, Huije; Lee, Jae Yoon; Seo, Dongjea; Watanabe, Kenji; Taniguchi, Takashi; Kim, Young Duck; Hone, James; Lee, Chul‐Ho; Lee, Gwan‐Hyoung
Abstract : In article 2003567, Chul‐Ho Lee, Gwan‐Hyoung Lee, and co‐workers report the development of a novel light‐emitting field‐effect transistor (LEFET) based on a van der Waals heterostructure. Multiple modes of operation are achieved by controlling the injection of holes and electrons in the graphene–WSe2 contacts. Effective recombination of excitons in the 2D layer enables high external quantum efficiency in the LEFET, which will play an important role in future optoelectronic circuits.